The sonic persona an anthropology of sound - Schulze, Holger; Bloomsbury Collections Online (Online service). (New York Bloomsbury Academic, an imprint of Bloomsbury Publishing Inc, 2018)
"Holger Schulze undertakes a critical study of some of the most influential studies in sound since the 19th century in the natural sciences, the engineering sciences, and in media theory, confronting them with contemporary artistic practices, with experimental critique, and with disturbing sonic experiences. From Hermann von Helmholtz to Miley Cyrus, from FLUXUS to the Arab Spring, from Wavefield Synthesis to otoacoustic emissions, from premillennial clubculture to postdemocratic authoritarianism, from signal processing to human echolocation, this book presents a fundamental critique concerning recent sound theories and their anthropological concepts--and proposes an alternate, a more plastic, a visceral framework for research in the field of a cultural anthropology of sounding and listening. This anthropology of sound takes its readers and listeners on a research expedition to the multitude of alien humanoids and their surprising sonic personae: in dynamic and generative tension between predetermined auditory dispositives, miniscule and not seldomly ignored sound practices, and idiosyncratic sensory corpuses: a critique of the senses"--Amazon.
Quantifying sound -- Materializing listening -- Corporealizing the senses -- In auditory dispositives -- The sonic persona -- A sensory corpus -- The precision of sensibility -- Resistance and resonance -- Generativity.
Includes bibliographical references (pages 233-245) and index.
Keywords: Sound; Senses and sensation -- Social aspects; Communication in anthropology; Electronic books